2011
DOI: 10.1364/ol.36.003109
|View full text |Cite
|
Sign up to set email alerts
|

Frequency noise of free-running 46 μm distributed feedback quantum cascade lasers near room temperature

Abstract: The frequency noise properties of commercial distributed feedback quantum cascade lasers emitting in the 4.6 μm range and operated in cw mode near room temperature (277 K) are presented. The measured frequency noise power spectral density reveals a flicker noise dropping down to the very low level of <100 Hz(2)/Hz at 10 MHz Fourier frequency and is globally a factor of 100 lower than data recently reported for a similar laser operated at cryogenic temperature. This makes our laser a good candidate for the real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 11 publications
9
54
0
Order By: Relevance
“…2 shows the resulting frequency noise power spectral density (PSD) of the QCL. It has a 1/f trend at low frequency, followed by a steeper slope above ∼ 300 kHz, as observed in 21,22 . Note however that the measured frequency noise PSD is roughly one order of magnitude lower than previously published characterizations of free-running cw-mode near-RT DFB QCLs 20-24 .…”
supporting
confidence: 52%
“…2 shows the resulting frequency noise power spectral density (PSD) of the QCL. It has a 1/f trend at low frequency, followed by a steeper slope above ∼ 300 kHz, as observed in 21,22 . Note however that the measured frequency noise PSD is roughly one order of magnitude lower than previously published characterizations of free-running cw-mode near-RT DFB QCLs 20-24 .…”
supporting
confidence: 52%
“…4,5 In order to push the limits of those highresolution experiments, narrow-linewidth sources of coherent light which can be achieved by active stabilization of DFB-QCLs to optical references with high-bandwidth servoloops are required. 6,7 For the most demanding applications in the field of high-resolution spectroscopy, frequency-noise analysis revealed that feedback loop bandwidths of several hundred of kHz are necessary for linewidth narrowing of DFB-QCLs. 7,8 While the picosecond carrier lifetime in QCLs allows a very fast modulation of the intensity above 10 GHz, 9,10 the modulation of the optical frequency-or wavelength-is limited by the thermal dynamics of the device.…”
mentioning
confidence: 99%
“…6,7 For the most demanding applications in the field of high-resolution spectroscopy, frequency-noise analysis revealed that feedback loop bandwidths of several hundred of kHz are necessary for linewidth narrowing of DFB-QCLs. 7,8 While the picosecond carrier lifetime in QCLs allows a very fast modulation of the intensity above 10 GHz, 9,10 the modulation of the optical frequency-or wavelength-is limited by the thermal dynamics of the device. Indeed, unlike interband semiconductor laser diodes whose wavelength can be modulated at high speed through carrier density modulation, 11,12 the latter has no effect in QCLs because of the symmetric gain curve and associated independence of the refractive index at the gain peak (zero alpha parameter).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optical frequency discriminators directly convert optical frequency fluctuations of the laser into intensity fluctuations that are detected by a photodetector. Optical discriminators are typically devices displaying a frequency-dependent transmission in a restricted frequency range, such as gas-filled cells near an atomic/molecular resonance (Doppler-broadened [10][11][12] or sub-Doppler 13 ), Fabry-Perot resonators 14 or unbalanced twobeam interferometers. 15 As it is not always possible to have a proper optical discriminator at the considered laser wavelength, another approach consists in heterodyning the laser under test with a second laser, either similar to the first one or with a negligible frequency noise, and subsequently analyzing the generated RF beat signal.…”
Section: Frequency Discriminatorsmentioning
confidence: 99%